Faktor-faktor yang Mempengaruhi Pengungkapan Tanggung Jawab Sosial Perusahaan - Ike Putri Wandriani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
The purpose of this research is to provide empirical evidence whether firm size, profitability, size of audit firm, leverage, net profit margin, and liquidity have influence to corporate social responsibility disclosure. This research used 60 samples of companies in the manufacturing sector that had been listed at the Indonesian Stock Exchange, within period from 2011 until 2013. Sample were obtained by purposive sampling method. Data were analyzed using multiple regression method. The result of this research showed that firm size, leverage, and net profit margin had influence toward corporate social responsibility disclosure. But in the contrary, profitability, size of audit firm, andliquidity had no influence toward corporate social responsibility disclosure.